TRIF signaling is required for caspase-11-dependent immune responses and lethality in sepsis - Yiting Tang; Rui Zhang; Qianqian Xue; Ran Meng; Xiangyu Wang; Yanliang Yang; Lingli Xie; Xianzhong Xiao; Timothy R. Billiar; Ben Lu (BMC, 2018)
Abstract Background Caspase-11, a cytosolic receptor of bacterial endotoxin (lipopolysaccharide: LPS), mediates immune responses and lethality in endotoxemia and experimental sepsis. However, the upstream pathways that regulate caspase-11 activation in endotoxemia and sepsis are not fully understood. The aim of this study is to test whether TIR-domain-containing adapter-inducing interferon-β (TRIF) signaling is critical for caspase-11-dependent immune responses and lethality in endotoxemia. Methods Mice of indicated genotypes were subjected to endotoxemia or cecum ligation and puncture (CLP) and monitored daily by signs of a moribund state for lethality. Serum interleukin (IL)-1α, IL-1β, IL-6 and tumor necrosis factor (TNF) were measured by ELISA. Data were analyzed by using student's t-test or one-way ANOVA followed by post-hoc Bonferroni test. Survival data were analyzed by using the log-rank test. Results Blockade of type 1 interferon signaling or genetic deletion of TRIF or guanylate-binding proteins (GBPs) prevented caspase-11-dependent immune responses, organ injury and lethality in endotoxemia and experimental sepsis. In vitro, deletion of GBPs blocked cytosolic LPS-induced caspase-11 activation in mouse macrophages. Conclusions These findings demonstrate that TRIF signaling is required for caspase-11-dependent immune responses and lethality in endotoxemia and sepsis, and provide novel mechanistic insights into how LPS induces caspase-11 activation during bacterial infection.